Parenting Together: Understanding the Shared Context of Positive Parenting Among Low-Income Black Families. (May 2020) - McWayne, Christine M.; Mattis, Jacqueline S.; Li, Lok-Wah
This study examined the relations between family demographics and positive parenting dimensions among urban-residing, low-income, Black caregiving dyads. Participants were 100 co-caregivers affiliated with a Head Start program and reporting on 50 preschool-aged children. Given that the parenting context for the caregiver pairs was not independent, multilevel dyadic analysis was employed to determine demographic predictors of positive parenting dimensions as measured by the emically derived Black Parenting Strengths in Context scale. Findings illuminated associations between combinations of adult/child characteristics (e.g., nativity, parental employment status, child gender) and the five dimensions of positive parenting measured (i.e., Fostering Connectedness; Racial and Cultural Pride; Involvement at School; Religious and Spiritual Practices; Behavioral Responsiveness and Guidance). Findings suggest implications for future research and theory involving Black family life—specifically the need to examine parenting by considering the combined effects of individual and shared family characteristics—and for designing parent support efforts that recognize family roles and heritages, and that leverage the strengths of and heterogeneity among the multiple caregivers in the lives of young children.